A Qualitative Study on Unassisted Smoking Cessation Among Chinese Canadian Immigrants - Aimei Mao PhD; Joan L. Bottorff PhD, RN, FCAHS, FAAN (American Journal of Men's Health, 2017)
It is well-known that majority of smokers worldwide quit smoking without any assistance. This is even more evident among Chinese smokers. The aim of this qualitative study was to explore how Chinese Canadian immigrant men who smoked cigarettes perceived smoking cessation aids and services and how they used any form of the smoking cessation assistance to help them quit smoking. The study was conducted in British Columbia, Canada. Twenty-two Chinese immigrants were recruited by internet advertisement and through connections with local Chinese communities. Ten of the 22 participants were current smokers and the other 12 had quit smoking in the past 5 years. Data were collected using semistructured interviews. Although all participants, including both the ex-smokers and current smokers, had made more than one quit attempt, they rarely used cessation aids or services even after they had immigrated to Canada. The barriers to seeking the cessation assistance were grouped into two categories: practical barriers and cultural barriers. The practical barriers included “Lack of available information on smoking cessation assistance” and “Difficulty in accessing smoking cessation assistance,” while cultural barriers included “Denial of physiological addiction to nicotine,” “Mistrust in the effectiveness of smoking cessation assistance,” “Tendency of self-reliance in solving problems,” and “Concern of privacy revelation related to utilization of smoking cessation assistance.” The findings revealed Chinese immigrants’ unwillingness to use smoking cessation assistance as the result of vulnerability as immigrants and culturally cultivated masculinities of self-control and self-reliance.